Production Of Xylose Reductase From Adapted Candida Tropicalis Grown In Sawdust Hydrolysate - M. Rafiqul, Islam; Mimi Sakinah, A. M. (Elsevier Ltd., 2014)
Xylose, recovered from Meranti wood sawdust (MWS), can be used as a promising and alternative carbon source for yeast growth as well as for the production of xylose reductase (XR). This enzyme has potential applications in the bioproduction of various high value products, especially xylitol. The aim of this study was to isolate XR from adapted yeast Candida tropicalis and to characterize it. The XR enzyme was prepared from C. tropicalis strain, grown in MWS hydrolysate-based medium, by ultrasonic homogenization. The isolated XR was characterized based on enzyme activity, stability, and kinetic constants. The activity of NADPH-dependent crude XR measured was 11.16 U/mL. It was stable at pH 5.0–7.0 and temperature of 25–40 1C for 24 h, and retained above 95% of its original activity after 4 months of storage at –80 1C. The apparent Km values of XR for xylose and NADPH were 81.78 mM and 7.29 μM while the Vmax for xylose and NADPH were 178.57 and 12.5 μM/min, respectively. The low Km,app and high Vmax,app values of XR for xylose as a substrate indicates a strong binding affinity for xylose and good productivity of the reaction.